Measuring Sustainable Livelihood for Malaysia’s Poor: The Sustainable Livelihoods Index and the B40 Group of Coastal Fishermen in Northern Peninsular Malaysia - Ibrahim, Ahmad Zubir; Hassan, Kalthum; Kamarudin, Roslina; Anuar, Abd Rahim (2018)
In developing countries such as Malaysia where the expressed goals are to improve the standard and quality of living of the most vulnerable sections of the community such as the hardcore poor concerted efforts are needed to strengthen and refine the measures of what constitute sustainable livelihood.This study examines the achievement of sustainable livelihood for poor coastal fishermen in Northern Peninsular Malaysia through the measurement of a sustainable livelihood index based on Sustainable Livelihood Analysis (SLA). Primary data on human, physical, financial, social and natural assets of the subjects for this quantitative study were gathered through the stratified sampling of 400 fishermen respondents from Kuala Kedah, Yan, Tanjung Dawai and Kuala Perlis.The SLA findings revealed that scores for financial assets of the fishermen were low compared to those of the other assets.Remedial measures were recommended which included providing grants for supporting micro-enterprises, increasing income through contract farming, and providing opportunities for expanding the application of the agropolitan concept to the coastal fishermen sector.